MODEL OF ARISAN AUCTION SYSTEM - (NIM: 20107046); Pembimbing Dr. Sri Redjeki Pujaprasetya F., AKIP
Differ from the Convensional Arisan which is usually carried out with the ballot. Arisan of Auction System is arisan carried out with the auction to determine the participants as the winner. The winner is the participant who has the most auctions, provided the participant of auction is participant who has not been declared as the winner. The size of the acquisition is the amount of the total number of contributions during arisan reduced by the auction. First, before the auction begins, the committee must determine the minimum auction as a benchmark. Minimal amount of the auction should not be too low or high. Because, if the minimal amount of the auction is too low at the beginning, then too many participants want to be a winner. If the minmal amount of the auction is too high at the end, then the participants will think they’re loss. For the cases of the number of arisan period equal to the number of participants, the auction is determined by using the minimal approach in that conpound interest that is paid continuously. ln this case, there is a final auction minimal negative at final times, which means the winner does not need to pay, even get some money. Although visibly less realistic, this model is still possible to be done. While for the cases of the number of the arisan period less then the number of participants, the auction is determined by using the minimal approach of arithmetic sequance. ln the second case, this can be made the simulation of some auction situations that allow the committee to plan for the process/ situation auction that desired. From the second approach, by using the calculation of compound interest that is paid continuously, there is a possibility that in the end, each participant can benefit relatively the same.